(untitled) (Vietnam Journal of Community Medicine, 2025)
Awake craniotomy combined with intraoperative electrophysiological monitoring helps to map the cerebral cortex, maximally removing the damaged brain area while preserving neurological function. For successful awake craniotomy, patient cooperation, pre- and intra-operative communication, and consensus among surgeons, anesthesiologists, and the OR staff are required. There is no recognized consensus on the best anaesthetic approach to an awake craniotomy. Based on the characteristics of each patient and surgery, we chose the Asleep-Awake-Asleep method for the surgery to remove the brain lesion causing epilepsy, and the Awake-Asleep method for the placement of deep brain stimulation. Scalp block plays an important role in pain management during awake craniotomy.